2022
DOI: 10.1002/ece3.8901
|View full text |Cite
|
Sign up to set email alerts
|

High genetic differentiation of Indo‐Pacific humpback dolphins (Sousa chinensis) along the Asian Coast of the Pacific Ocean

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…species/subspecies delimitation; Jefferson & Rosenbaum, 2014; Wang, Yang & Hung, 2015), population history (e.g. divergence, population structure; Zhao et al, 2021; Dai et al, 2022) and differentiation (e.g. genetic diversity, gene flow, isolation; Parra et al, 2018; Amaral et al, 2020; Lampert et al, 2021) of humpback dolphins.…”
Section: Genetics: Genetic Diversity and Population Isolationmentioning
confidence: 99%
“…species/subspecies delimitation; Jefferson & Rosenbaum, 2014; Wang, Yang & Hung, 2015), population history (e.g. divergence, population structure; Zhao et al, 2021; Dai et al, 2022) and differentiation (e.g. genetic diversity, gene flow, isolation; Parra et al, 2018; Amaral et al, 2020; Lampert et al, 2021) of humpback dolphins.…”
Section: Genetics: Genetic Diversity and Population Isolationmentioning
confidence: 99%
“…To my knowledge, it is not yet known how admixture of different clusters progresses by individual dispersal at the population level during density fluctuations. Clustering analysis has been used to evaluate the spatial genetic structure and admixture of lineages (Beichman et al, 2023 ; Dai et al, 2022 ; Flucher et al, 2021 ; Krojerová‐Prokešová et al, 2015 ). Only a few studies have revealed temporal changes in cluster admixture proportions.…”
Section: Introductionmentioning
confidence: 99%